Nuevas técnicas para cálculos fuera de la capa de masa en Teoría de norma y gravedad - Ahmadiniaz, Naser (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
At the most fundamental level, the constituent blocks of the universe interact in four different ways as far as known, namely, strongly and weakly and subnuclear scales, as well as electromagnetically and gravitationally at scales that could be even macroscopical, of the size of the Universe itself. At the scale energies explored in large particle accelerators, it has been determined that weak and electromagnetic are but two sides of a single fundamental interaction, the electroweak interaction. On the other side, what holds nuclei together is the strong interaction of quantum chromodynamics (QDC). QCD and the electroweak theory are described in the elegant language of quantum field theory in the celebrated Standard Model of Particle Physics. At the tested scales, gravitational interactions are irrelevant for elementary particles. Nevertheless, either at the early universe or near strong gravitational fields, gravitational interaction has to be taken into account in order to have a realistic microscopic description. In high energy experiments, fundamental interactions allow a perturbative description in terms of Feynman Diagrams. The second quantization methods - often employed in such a description- soon become inefficient as the number of Feynman diagrams required for a precise description of a given process grows with the order of approximation. Alternatively, first quantization methods such as the worldline formalism offer a different framework for the calculation of scattering amplitudes for fundamental interactions, including gravitational interaction. They may help to get a systematic computation of (classes of) scattering amplitudes. This is a task that traditional methods has failed to achieve. Although the (string inspired) worldline formalism is not a recent proposal, only in the last decades it has become a powerful tool as an alternative to conventional second-quantized methods.

Al nivel más fundamental, los constituyentes fundamentales del universo interactúan de cuatro formas distintas, fuerte y débilmente, por un lado a distancias subnucleares y electromagnética y gravitacionalmente a escalas que pueden ser incluso macroscópicas. Las interacciones electrodébiles y fuertes se describen en el lenguaje de la teoría cuántica de campos en el Modelo Estándar de Partículas Fundamentales, que a las escalas experimentales explorada considera las interacciones gravitacionales irrelevantes. Sin embargo, en situaciones como en el Universo temprano la interacción gravitacional debe incluirse para tener una descripción microscópica realista. A muy altas energías, las interacciones fundamentales permiten una descripción perturbativa en términos de Diagramas de Feynman. Los métodos de la segunda Cuantización comúnmente usados se vuelven ineficientes rápidamente en el sentido del gran número de diagramas que deben calcularse para una descripción más precisa de un proceso dado. Alternativamente, los métodos de primera Cuantización ofrecen un escenario en el que el cálculo de amplitudes para procesos de interacciones fundamentales, con la inclusión particular de la interacción gravitacional, pueden ser tratables y susceptibles de mejoras sistemáticas donde los métodos tradicionales fallan. Si bien los métodos basados en formalismo de línea de mundo, inspirado en la teoría de cuerdas, no son recientes, su aplicabilidad y eficiencia ha alcanzado un nivel predictivo que compite con los esquemas tradicionales. En esta tesis aplicamos dichos métodos a cuatro diferentes problemas: Un análisis en el rango entero de masas de la acción efectiva de QED en un fondo con simetría O(2) x O(3) y la representación de línea de mundo del vértice tres gluones y el vértice de cuatro gluones, así como la amplitud fotón gravitón. Esta tesis está organizada de la siguiente manera: El Capítulo 1 presenta una introducción al formalismo de línea de mundo.
Instituto de Física y Matemáticas. Doctorado en Ciencias en el Área de Física
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2212; info:eu-repo/classification/cti/1; IFM-D-2014-1379; Formalismo; QED; QCD